Towards Polyionic Liquid-Based Supports for Application in Biocatalysis - Mohd Amin, Nur Amalina (2019)
This thesis describes the utilisation of PILs as the carrier matrices to improve the stability of transaminase enzymes in catalysing chiral amine formation and to ease their subsequent removal from reaction media. The synthesis of the ionic liquid monomers having polymerising groups on the cations has been investigated. These ionic liquid monomers act as the main components for immobilised enzyme carrier matrices. This has included ionic liquids which consisted of variable alkyl chain length on the cation and ionic liquids with different cation and anion combinations. The effects of ionic liquid anions and cations variations to their structure, thermal and optical properties were assessed by using the instrumentation techniques.